Capacidade institucional do Tribunal de Contas do Estado de Mato Grosso : o caso do Veículo Leve sobre Trilhos (VLT) - Contrera, Renata Bueno (2020)
The Federal Constitution of 1988 (CF / 88) expanded the powers and duties of the control and inspection bodies of the Public Administration. Among these, the Courts of Accounts stand out, which have the constitutional participation in monitoring and inspecting the performance of public bodies. These are well-equipped organizations with trained bureaucracies to control the actions of public administration, but in which these cases can become dysfunctional. In Mato Grosso, the performance of the State Audit Court (TCE-MT) did not prevent the problems of planning and execution the implementation of the Light Rail Vehicle (VLT) in Cuiabá and Várzea Grande. The objective of this research is to analyze the development, design and institutional capacities of TCE-MT, and to what extent these aspects influenced the agency's ability to carry out its task of supervising the implementation of the VLT in Cuiabá and Várzea Grande. The hypothesis built suggests that the political appointment of the TCE-MT board members makes it difficult for them to act as a control agency. To this end, it used data related to the performance of TCE-MT in the inspection of VLT works. To carry out the research, the following methodological procedures were used: literature review; semi-structured interviews; analysis of official documents and reports from the control agencie. The analysis of the data indicates that the institutional design of the TCE MT affected the inspection of the VLT, which was influenced by the political environment.